2013
DOI: 10.1152/ajpcell.00412.2012
|View full text |Cite
|
Sign up to set email alerts
|

Volume-sensitive release of organic osmolytes in the human lung epithelial cell line A549: role of the 5-lipoxygenase

Abstract: Holm JB, Grygorczyk R, Lambert IH. Volume-sensitive release of organic osmolytes in the human lung epithelial cell line A549: role of the 5-lipoxygenase. Am J Physiol Cell Physiol 305: C48-C60, 2013. First published March 13, 2013; doi:10.1152/ajpcell.00412.2012.-Pathophysiological conditions challenge cell volume homeostasis and perturb cell volume regulatory mechanisms leading to alterations of cell metabolism, active transepithelial transport, cell migration, and death. We report that inhibition of the 5-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 73 publications
3
52
1
Order By: Relevance
“…[ 3 H]taurine (PerkinElmer, Waltham, MA) was used to estimate the uptake of taurine via TauT as well as the efflux under isotonic and hypotonic conditions as previously described (19,61). All the experiments were performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 H]taurine (PerkinElmer, Waltham, MA) was used to estimate the uptake of taurine via TauT as well as the efflux under isotonic and hypotonic conditions as previously described (19,61). All the experiments were performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the active taurine uptake system involving TauT, taurine release involves 1) volume-sensitive leak pathways, activated by osmotic cell swelling [termed the volumesensitive organic anion channel (VSOAC)]; and 2) volumeinsensitive leak pathways, activated during anoxia, apoptosis, and cholesterol depletion (27,31,45,61). With the use of EATC and the human lung epithelial cell line A549, it has been demonstrated that swelling-induced activation of VSOAC involves phospholipase A 2 (PLA 2 ) and 5-lipoxygenase (5-LO) activity as well as binding of eicosanoids to the cysteinyl leukotriene 1 receptor CysLT1 (19,27). Once activated VSOAC activity is modulated by phosphatases, i.e., inhibition of vanadate-sensitive protein tyrosine phosphatases by ROS, which are generated in a variety of cells in response to osmotic perturbation, or inhibition of the phosphatidylinositol (3,4,5)-trisphosphate phosphatase PTEN (phosphatase and tensin homologue), leads to significant potentiation of taurine loss following exposure to hypotonic conditions (12,26,28,31).…”
mentioning
confidence: 99%
“…78 Hence, inhibition of VRAC blocks AVD and cell death. 74,75,78,79 Activation of VRAC by apoptotic stimuli under isovolumetric conditions necessitates a shift in the volume set-point for VRAC toward a lower value. 35 Following the increased Cl -conductance during AVD, the cells depolarize which facilitates apoptotic K C loss.…”
Section: Vrac In Apoptosis and In Multidrug Resistancementioning
confidence: 99%
“…Cell shape changes rely on the spatial and temporal coordination of biochemical and physical processes at the molecular, cellular and tissue scale, and the homeostasis of cell volume is a major challenge for eukaryotic cells and tissues [57][58][59][60]. Cell volume and morphology may vary considerably under different environmental conditions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%